A New Species of Macellicephaloides Uschakov, 1955 (Annelida, Polynoidae) from Cold Seeps in the South China Sea: Insights into the Taxonomy and Phylogeny of Macellicephaloides and Related Genera - Li, Jie; Zhang, Linlin; Wang, Mingxiao; Wu, Xuwen (Current Issues in Molecular Biology, 2025)
Macellicephaloides Uschakov, 1955 (Annelida: Polynoidae) is a genus of deep-sea polychaetes characterized by a specialized pharynx bearing two pairs of jaws (with the dorsal pair fused) and three pairs of lateral papillae, the middle pair of which is greatly elongated, and remarkable adaptability to diverse deep-sea habitats. Most species in this genus inhabit abyssal depths (>7200 m), with high diversity in western Pacific trenches, while a few occur in relatively shallow habitats such as deep-sea seamounts and hydrothermal vents. This paper presents a new species, Macellicephaloides lingshuiensis sp. nov., found in deep-sea cold seeps in the South China Sea, representing the shallowest distribution record for the genus to date and the first record from cold seep environments. The classification and phylogeny of Macellicephaloides and related genera have long been the subject of debate. A previous study suggested that Macellicephaloides is nested within the Macellicephala clade, but our analyses—based on 13 mitochondrial protein-coding genes, 12S, 16S, 18S, 28S rRNA, and ITS1-ITS2 sequences—tentatively indicate that these two genera form independent evolutionary clades. Additionally, our phylogeny indicates a close evolutionary relationship between deep-sea Macellicephaloides and cave-dwelling polynoids (e.g., Gesiella), highlighting ecological connections between deep-sea and cave habitats. These conclusions are supported by morphological comparisons and genetic distance analyses. Although the subfamily Macellicephalinae is recovered as a monophyletic group, intergeneric phylogenetic relationships within it remain unresolved, highlighting the need for additional data from more species and genera. We amend the generic diagnosis of Macellicephaloides and provide an identification key to all valid species in the genus. This study clarifies the taxonomy and phylogeny of Macellicephaloides and related taxa, emphasizing the importance of continued sampling in understudied deep-sea habitats to enhance our understanding of their biodiversity.